Us Unilateral Sanctions Against Iran; Contradiction in Slogan and Conduct, Extreme Politisization of Human Rights - Seyd Fazollah Mousavi; Fazllolah Jokar; Omran Mohammadi (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2015)
Human rights as a prominent discourse has gained so much weight in International area and governments legitimacy is generally and increasingly evaluated upon the extent to which they adhere to its rules and principles. Almost all and any conduct in international relations is to comply with human rights including sanctions are imposed by UN Security Council and embargoes have been set unilaterally by states.  Islamic Republic of Iran for long confronted with embargoes unilaterally imposed by USA and EU. These embargoes have been expansive with serious adverse effects on the nation. This paper is aimed at finding whether sanctions may lead to violation of human rights in Iran and as far as  Iranian nationals  are concerned, which category of human rights are so violated? The hypothesis here is that the US unilateral embargoes have in different ways led to violation of human rights in Iran.